Pelatihan Hospitality Untuk Meningkatkan Kualitas Pelayanan Di Desa Wisata Batu Kumbung - Putu Herny Susanti; Ni Putu Dhyanantari Putri; I Kadek Agus Suartana; Ni Putu Kris Pradnya Swari; Maria Sri Utami (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Batu Kumbung Tourism Village possesses considerable cultural tourism potential that requires competent human resources capable of delivering high-quality visitor services. However, the community's understanding of hospitality principles remains limited and needs to be strengthened to create positive visitor experiences. This community service program aimed to improve the knowledge and practical skills of local communities in implementing hospitality within tourism services. The program was conducted from May 21–23, 2026, using a participatory approach involving members of Pokdarwis, village officials, local micro and small business owners, tourism attraction managers, and community members. The training employed interactive lectures, participatory discussions, and evaluations through observation and questionnaires. The results demonstrated an improvement in participants' understanding of hospitality, excellence service, effective communication, and the importance of creating positive visitor experiences. The evaluation also identified several capacity-building needs, including communication skills, foreign language proficiency, complaint handling, and tour guiding competencies. Overall, the program contributed to strengthening community capacity and provides a foundation for sustainable follow-up assistance to support the development of Batu Kumbung Tourism Village as a culturally based tourism destination.